To perform the operation, we will subtract each term individually:
First, subtract the x^3 terms: -5x^2 - (-3x^3) = -5x^2 + 3x^3
Then, subtract the x term: 5x - x = 4x
Finally, subtract the constant terms: -5 - 0 = -5
Therefore, the result of the operation is:
4x^3 - 5x^2 + 4x - 5
Perform the operation.
(-5x^2 + 5x - 5) - (3x^3+ x)
19 answers
subtract -9x^2 + 4x from -8x^2 + 8x - 10
To subtract -9x^2 + 4x from -8x^2 + 8x - 10, we need to change the signs of each term in -9x^2 + 4x and then add them to the corresponding terms of -8x^2 + 8x - 10.
So, the result of the operation is:
(-8x^2 + 8x - 10) - (-9x^2 + 4x)
= -8x^2 + 8x - 10 + 9x^2 - 4x
= (-8x^2 + 9x^2) + (8x - 4x) - 10
= x^2 + 4x - 10
Therefore, the result of the operation is x^2 + 4x - 10.
So, the result of the operation is:
(-8x^2 + 8x - 10) - (-9x^2 + 4x)
= -8x^2 + 8x - 10 + 9x^2 - 4x
= (-8x^2 + 9x^2) + (8x - 4x) - 10
= x^2 + 4x - 10
Therefore, the result of the operation is x^2 + 4x - 10.
Use multiplication to fully expand the expression below.
A^5 c^2
A^5 c^2
To fully expand the expression A^5 c^2, we need to multiply the variables A and c together, and also raise each variable to the power of 5 and 2, respectively.
Therefore, the fully expanded expression is:
(A^5) * (c^2) = (A * A * A * A * A) * (c * c)
= A^5 * c^2
= A * A * A * A * A * c * c
= AAAAA * cc
= AAAAAcc
So, the fully expanded expression is AAAAAcc.
Therefore, the fully expanded expression is:
(A^5) * (c^2) = (A * A * A * A * A) * (c * c)
= A^5 * c^2
= A * A * A * A * A * c * c
= AAAAA * cc
= AAAAAcc
So, the fully expanded expression is AAAAAcc.
Simplify
(x^4)^5
(x^4)^5
To simplify (x^4)^5, we need to raise x^4 to the power of 5. This means we will multiply the exponents:
(x^4)^5 = x^(4*5) = x^20
So, the simplified expression is x^20.
(x^4)^5 = x^(4*5) = x^20
So, the simplified expression is x^20.
Use multiplication to expand the expression below. Then compute and/or simplify.
(3y)^5
Press the • button or type the * symbol on your keyboard to represent multiplication. Usin multiplication is inappropriate when x may be used as a variable. For the answer, type the use the a" button or type the ^ symbol for an exponent.
Expanded form:
Answer:
(3y)^5
Press the • button or type the * symbol on your keyboard to represent multiplication. Usin multiplication is inappropriate when x may be used as a variable. For the answer, type the use the a" button or type the ^ symbol for an exponent.
Expanded form:
Answer:
The expanded form of (3y)^5 is:
(3y)^5 = (3y)(3y)(3y)(3y)(3y)
Simplifying further:
= 3^5 * y^5
= 243y^5
Therefore, the expanded form of (3y)^5 is 243y^5.
(3y)^5 = (3y)(3y)(3y)(3y)(3y)
Simplifying further:
= 3^5 * y^5
= 243y^5
Therefore, the expanded form of (3y)^5 is 243y^5.
You can only use letters for the answer part
I apologize for the mistake. The correct answer, using only letters, is:
(3y)^5 = 3^5 * y^5 = 243y^5
(3y)^5 = 3^5 * y^5 = 243y^5
Simplify
(3k^4)(7k^5)
(3k^4)(7k^5)
To simplify (3k^4)(7k^5), we multiply the coefficients (3 and 7) and add the exponents of k:
(3k^4)(7k^5) = (3 * 7)(k^4 * k^5) = 21k^(4 + 5) = 21k^9
Therefore, the simplified form is 21k^9.
(3k^4)(7k^5) = (3 * 7)(k^4 * k^5) = 21k^(4 + 5) = 21k^9
Therefore, the simplified form is 21k^9.
Simplify
(4p^2)^3
(4p^2)^3
To simplify (4p^2)^3, we raise both the coefficient and the exponent inside the parentheses to the power of 3:
(4p^2)^3 = 4^3 * (p^2)^3 = 64p^(2*3) = 64p^6
Therefore, the simplified form is 64p^6.
(4p^2)^3 = 4^3 * (p^2)^3 = 64p^(2*3) = 64p^6
Therefore, the simplified form is 64p^6.
Fully simplify
x^4y^2(2x^2)
x^4y^2(2x^2)
To fully simplify the expression x^4y^2(2x^2), we multiply the coefficients and combine the like terms by adding the exponents of x and y:
x^4y^2(2x^2) = 2x^(4+2)y^2 = 2x^6y^2
Therefore, the fully simplified form is 2x^6y^2.
x^4y^2(2x^2) = 2x^(4+2)y^2 = 2x^6y^2
Therefore, the fully simplified form is 2x^6y^2.
This is wrong
You are correct, my previous response was incorrect. I apologize for the mistake.
To simplify x^4y^2(2x^2), we apply the distributive property of multiplication.
x^4y^2(2x^2) = 2x^4y^2 * x^2
Multiplying the coefficients, we have:
2 * 1 = 2
Adding the exponents of x, we have:
x^4 * x^2 = x^(4+2) = x^6
Therefore, the simplified form is:
2x^6y^2
To simplify x^4y^2(2x^2), we apply the distributive property of multiplication.
x^4y^2(2x^2) = 2x^4y^2 * x^2
Multiplying the coefficients, we have:
2 * 1 = 2
Adding the exponents of x, we have:
x^4 * x^2 = x^(4+2) = x^6
Therefore, the simplified form is:
2x^6y^2